2016
DOI: 10.1002/pc.24109
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of unilateral conductive and transparent polymer thin films decorated with nanomaterials for flexible electrodes

Abstract: Recently, electrically conductive, flexible, and transparent nanocomposite thin films consisting of nanomaterials on insulating polymer layers are of particular interest to scientific and industrial experts and have promising applications in energy, electronic, and environment areas, due to their remarkable properties. In this study, nanomaterials including silver nanowires, reduced graphene oxide, and carbon nanotubes, and also, conducting polymer poly(3,4‐ethylenedioxythiophene):polystyrene sulfonate were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…and high optical transmittance (80%), and the electrical conductivity remained stable over 3K bending [117]. In addition, Mahmut et al found that unidirectional conductive transparent films can be prepared by embedding nanomaterials into polymer membranes (Figure 8) [9].…”
Section: Conductive Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…and high optical transmittance (80%), and the electrical conductivity remained stable over 3K bending [117]. In addition, Mahmut et al found that unidirectional conductive transparent films can be prepared by embedding nanomaterials into polymer membranes (Figure 8) [9].…”
Section: Conductive Polymersmentioning
confidence: 99%
“…Zhu et al used a combination of printing, evaporation, and wet etching techniques to produce transparent micromesh electrodes with high conductivity (19.7 Ω•sq −1 ) and high optical transmittance (80%), and the electrical conductivity remained stable over 3K bending [117]. In addition, Mahmut et al found that unidirectional conductive transparent films can be prepared by embedding nanomaterials into polymer membranes (Figure 8) [9]. ) and high optical transmittance (80%), and the electrical conductivity remained stable over 3K bending [117].…”
Section: Conductive Polymersmentioning
confidence: 99%
See 1 more Smart Citation